2014
DOI: 10.5194/acp-14-399-2014
|View full text |Cite
|
Sign up to set email alerts
|

The Atmospheric Infrared Sounder version 6 cloud products

Abstract: Abstract. The version 6 cloud products of the Atmospheric Infrared Sounder (AIRS) and Advanced Microwave Sounding Unit (AMSU) instrument suite are described. The cloud top temperature, pressure, and height and effective cloud fraction are now reported at the AIRS field-of-view (FOV) resolution. Significant improvements in cloud height assignment over version 5 are shown with FOV-scale comparisons to cloud vertical structure observed by the CloudSat 94 GHz radar and the Cloud-Aerosol LIdar with Orthogonal Polar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
88
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 107 publications
(90 citation statements)
references
References 117 publications
2
88
0
Order By: Relevance
“…This was a dramatically different measurement obtained from thermal infrared spectra with a coarse 13.5 km footprint rather than reflected solar energy at fine spatial resolution. Kahn et al (2014) detail the algorithm, and Jin and Nasiri (2014) validate it using pixel-scale comparisons with CALIPSO data. We filtered clouds using an AIRS sensitivity threshold (effective cloud fraction, or ECF) of 0.1 and binned AIRS phases by latitude and season for direct comparison.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This was a dramatically different measurement obtained from thermal infrared spectra with a coarse 13.5 km footprint rather than reflected solar energy at fine spatial resolution. Kahn et al (2014) detail the algorithm, and Jin and Nasiri (2014) validate it using pixel-scale comparisons with CALIPSO data. We filtered clouds using an AIRS sensitivity threshold (effective cloud fraction, or ECF) of 0.1 and binned AIRS phases by latitude and season for direct comparison.…”
Section: Methodsmentioning
confidence: 99%
“…The article first describes our estimation method, and reports seasonal and latitudinal changes of cloud thermodynamic phase. We then compare these distributions to measurements by NASA's Atmospheric Infrared Sounder (AIRS) (Kahn et al, 2014). Finally, we show the spatial scaling properties of both extratropical and tropical cloud populations.…”
Section: Introductionmentioning
confidence: 99%
“…Global decadal-scale satellite-based estimates of r ei are available from two algorithm versions of the Moderate Resolution Imaging Spectroradiometer (MODIS) (Platnick et al, 2017;Minnis et al, 2011) and the Atmospheric Infrared Sounder (AIRS) (Kahn et al, 2014;Teixeira, 2013). Another estimate of r ei is derived from a combination of the CloudAerosol Lidar with Orthogonal Polarization (CALIOP) and the Imaging Infrared Radiometer (IIR) instruments (Garnier et al, 2013) on the Cloud-Aerosol Lidar and Infrared Pathfinder Satellite Observation (CALIPSO) satellite (Winker et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The vertical heterogeneity of ice water content (IWC) and r ei are known to cause differences in r ei derived from shortwave/near-infrared (SWIR) and mid-infrared (MIR) bands for identical clouds and observing geometry (Zhang et al, 2010). Kahn et al (2015) compared pixel-scale retrievals between MODIS Collection 6 (C6; Platnick et al, 2017) and AIRS Version 6 (V6; Kahn et al, 2014) and confirmed, for a small subset of homogeneous clouds, that r ei is typically 5-10 µm larger when derived from MODIS SWIR bands compared to AIRS MIR bands.…”
Section: Introductionmentioning
confidence: 99%
“…A good example is the use of MODIS imageries in the CERES SSF algorithm. Another example is the use of microwave sounding observations to help the surface parameter retrievals, which in turn helps the retrievals of atmospheric parameters including the cloud vs. clear-sky detection (Kahn et al, 2014).…”
Section: Conclusion and Discussionmentioning
confidence: 99%